2019
DOI: 10.1038/s41598-019-55784-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the maximum number of layers in chemically exfoliated graphene

Abstract: An efficient route to synthesize macroscopic amounts of graphene is highly desired and bulk characterization of such samples, in terms of the number of layers, is equally important. We present a Raman spectroscopy-based method to determine the typical upper limit of the number of graphene layers in chemically exfoliated graphene. We utilize a controlled vapour-phase potassium intercalation technique and identify a lightly doped stage, where the Raman modes of undoped and doped few-layer graphene flakes coexist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 72 publications
1
20
0
Order By: Relevance
“…S5), crystallinity (Fig. S4, Table 3) [8][9][10][11][12][13][14][15][16][17][18][19]. The FWHM and intensity values of D and G mode indicate the distance between point-like defects smaller than 3 nm [19], for which phenomenological evaluation of distance between defects proposed by Concado et al [19] is not valid.…”
Section: Structural Properties Of Graphene Flakes By Raman Spectroscopymentioning
confidence: 94%
See 2 more Smart Citations
“…S5), crystallinity (Fig. S4, Table 3) [8][9][10][11][12][13][14][15][16][17][18][19]. The FWHM and intensity values of D and G mode indicate the distance between point-like defects smaller than 3 nm [19], for which phenomenological evaluation of distance between defects proposed by Concado et al [19] is not valid.…”
Section: Structural Properties Of Graphene Flakes By Raman Spectroscopymentioning
confidence: 94%
“…Description of structural and chemical properties of graphene materials basing on results obtained using X-ray photoelectron spectroscopy (XPS), X-ray excited Auger electron spectroscopy (XAES), reflection electron energy loss spectroscopy (REELS), Raman spectroscopy, X-ray diffraction (XRD), transmission electron microscopy (TEM), Fourier transformed infrared spectroscopy (FTIR), atomic force microscopy (AFM), etc., has been often reported [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. The FTIR and XPS analyses are usually applied for probing the chemical properties of atoms, carbon hybridizations and oxygen groups, where FTIR analysis information is related to the bulk, and XPS information depth is limited to the surface, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27] Chemical exfoliation was finalized using ultrasound tip sonication, as it is known to produce the best quality. [28,29] The properties of the starting material are well characterized by atomic force microscopy and Raman spectroscopy, which revealed that the restacked FLG is also present in the sample. [29] The dominant portion (90%) of the material consists of five layers or less, including monolayer content.…”
Section: Methods and Sample Preparationmentioning
confidence: 99%
“…[28,29] The properties of the starting material are well characterized by atomic force microscopy and Raman spectroscopy, which revealed that the restacked FLG is also present in the sample. [29] The dominant portion (90%) of the material consists of five layers or less, including monolayer content. Prior to in situ measurements, the undoped FLG was heated to 400 C for 30 min in high vacuum (2 Â 10 À6 mbar) to remove any residual solvents.…”
Section: Methods and Sample Preparationmentioning
confidence: 99%